A simple method for lodging resistance evaluation of maize in the field - Yang, Jinsheng; Meng, Xiangzeng; Yang, Shuangyuan; Yang, Jinzhong; Li, Zhaoxia; Yang, Qinglong; Zheng, Peifeng; Shao, Xiwen; Wang, Yongjun; Wang, Lichun (Frontiers in Plant Science, 2023)
The increase of planting density is a dominant approach for the higher yield of maize. However, the stalks of some varieties are prone to lodging under high density conditions. Much research has been done on the evaluation of maize lodging resistance. But there are few comprehensive reports on the determination of maize lodging resistance in situ without injury under field conditions. This study introduces a non-destructive in situ tester to determine the lodging resistance of the different maize varieties in the field. The force value can be obtained by pulling the stalk to different angles with this instrument, which is used to evaluate the lodging resistance of maize varieties. From 2018 to 2020, a total of 1,172 sample plants from 113 maize varieties were tested for the lodging resistance of plants. The statistical results show that the values of force on maize plants at 45° inclination angles (F45) are appropriate to characterize maize lodging resistance in situ by nondestructive testing in the field. According to the F45 value, the maximum lodging resistance Fmax can be inferred. The formula is: Fmax =1.1354 F45 – 0.3358. The evaluation results of lodging resistance of different varieties of this study are basically consistent with the test results of three-point bending method, moving wind tunnel and other methods. Therefore, the F45 value is the optimal index for nondestructive evaluation of maize stalk-lodging resistance under the field-planting conditions.